2005
DOI: 10.1593/neo.05106
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Interactions of HER-2, HPV-16 Oncoproteins in the Malignant Transformation of Human Mammary Epithelial Cells

Abstract: To better understand the mechanisms of transformation by the oncogene HER-2, we transduced the human mammary epithelial (HME) cell line MCF-10A with HER-2 and developed a cell line that appeared to moderately overexpress HER-2. These MCF-10HER-2 cells were unable to grow in the absence of epidermal growth factor (EGF). However, coexpression of HER-2 with the HPV-16 oncoproteins E6 and E7 resulted in EGF-independent cells that expressed very high levels of constitutively activated HER-2. Interestingly, coexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
3
29
0
1
Order By: Relevance
“…Furthermore, ErbB2 mRNA levels were not altered in the presence of HPV16 E6 (Figure 5a). Increase in ErbB2 transgene levels in HPV16 E6 and E7 expressing human mammary epithelial cells has been reported (Gewin et al, 2004;Woods Ignatoski et al, 2005). Thus HPV16 E6 might upregulate ErbB2 expression through translational as well as post-translational modifications and the detailed molecular mechanisms underlying postconfluent regulation of ErbB2 by E6-targeted proteins should be addressed further.…”
Section: Chxmentioning
confidence: 96%
“…Furthermore, ErbB2 mRNA levels were not altered in the presence of HPV16 E6 (Figure 5a). Increase in ErbB2 transgene levels in HPV16 E6 and E7 expressing human mammary epithelial cells has been reported (Gewin et al, 2004;Woods Ignatoski et al, 2005). Thus HPV16 E6 might upregulate ErbB2 expression through translational as well as post-translational modifications and the detailed molecular mechanisms underlying postconfluent regulation of ErbB2 by E6-targeted proteins should be addressed further.…”
Section: Chxmentioning
confidence: 96%
“…The MCF10A human mammary epithelial cell line and SUM44 breast cancer cell line were cultured as described previously (Forozan et al, 1999;Woods Ignatoski et al, 2005). MCF10Lsm1 cells were cultured in MCF10A medium with the antibiotic blasticidin (10 mg/ml) and without insulin.…”
Section: Cell Culture Conditionsmentioning
confidence: 99%
“…Cell lysis and protein quantification were performed as described previously (Woods Ignatoski et al, 2005). For IRS-1 immunoprecipitation, cell lysate (1 mg) was incubated with 2 mg/mg of IRS-1 antibody for 2 h at 41C followed by incubation with protein A/G agarose beads (Sigma) for 1 h at 41C.…”
Section: Immunoprecipitation and Western Blotsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) histology, and immunohistochemical analyses for ErbB-2 and b-catenin of tumors derived from the transgenic mice cells were performed as previously described in ref. 15 except that anti-b-catenin mAb (clone 14, Bio/Can Scientific) was used for the immunohistochemistry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…14 Recently, Woods Ignatoski et al reported that E6/E7 of HPV type 16 and ErB-2 cooperate with endogenous epidermal growth factor-receptor (EGF-R/ErbB1) to fully transform human breast immortalized cell line, MCF-10A. 15 Our group has developed a new in vitro model to study the effects of E6/E7 of HPV type 16 and ErbB-2 in human normal oral epithelial (NOE) cells. Using this model, we demonstrated that E6/E7 cooperates with ErbB-2 receptor to induce cellular transformation of NOE via the conversion of b-catenin from a cell-adhesion molecule to a potential transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%